Aplikasi Lima Kunci Keamanan Pangan dalam Pemilihan Pangan Jajanan Anak Sekolah (PJAS) oleh Murid SD Inpres Bertingkat Kelapa Lima II Kota Kupang - Marselinus Laga Nur; Anna Henny Talahatu; Christine Rohani Tadjo Tallo (Lontar : Journal of Community Health, 2019)
Street Food provides an important contribution to the fulfillment of children's energy while in school, but street food is very risky for biological, physical, and chemical contamination. These problems caused by several factors, namely the knowledge, attitudes, and actions of the makers, sellers, and buyers, about the importance of food security. Therefore, one of the efforts made by the government to overcome food insecurity is by educating five keys of food safety measures for the school community, students, and vendors of Pupils street food. This study is descriptive research that aims to know the knowledge and attitudes of the pupils in choosing food and vendors in processing street food at SD Inpres Bertingkat Kelapa Lima II Kota Kupang dealing with the five food security keys. The samples in this study were 52 students and 4 food vendors. The results showed that the knowledge of 52 student respondents, specifically 35 (67.3%) students had good knowledge, 14 (26.9%) students had sufficient knowledge, and 3 (5.8%) students had less knowledge. The attitude of 52 Respondents were categorized as Positive (100%). The respondent's actions based on triangulation revealed that the most of respondents still had actions that were not in accordance with the 5 keys food safety measures in the Selection of Snacks for Students.